2004
DOI: 10.1016/j.femsim.2004.05.012
|View full text |Cite
|
Sign up to set email alerts
|

Impact of drug resistance on fitness of Mycobacterium tuberculosis strains of the W-Beijing genotype

Abstract: Mycobacterium tuberculosis strains of the W-Beijing genotype became a common cause of tuberculosis during the past years and they are often associated with drug resistance. The biological factors facilitating the selection and wide dissemination of these strains are not known. To determine how acquisition of drug resistance affected growth of strains of the W-Beijing genotype, the growth of 55 M. tuberculosis isolates were studied using the BBL MGIT Mycobacteria Growth Indicator Tube and the BACTEC MGIT 960 Sy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

4
43
2
1

Year Published

2006
2006
2015
2015

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 64 publications
(50 citation statements)
references
References 23 publications
4
43
2
1
Order By: Relevance
“…Its ability to replace resident strains was demonstrated in a community-based study in Cape Town that prospectively tracked the rapid emergence of Beijing genotype strains over a 12-year period (44). The success and global spread of the Beijing genotype has been ascribed to multiple factors (45), including resistance to Mycobacterium bovis BCG-induced immunity (46), potential hypervirulence, and reduced fitness costs associated with the acquisition of drug resistance (47). The resolution of Beijing genotype strains was enhanced by 24-MIRU typing relative to the 12-MIRU typing.…”
Section: Discussionmentioning
confidence: 99%
“…Its ability to replace resident strains was demonstrated in a community-based study in Cape Town that prospectively tracked the rapid emergence of Beijing genotype strains over a 12-year period (44). The success and global spread of the Beijing genotype has been ascribed to multiple factors (45), including resistance to Mycobacterium bovis BCG-induced immunity (46), potential hypervirulence, and reduced fitness costs associated with the acquisition of drug resistance (47). The resolution of Beijing genotype strains was enhanced by 24-MIRU typing relative to the 12-MIRU typing.…”
Section: Discussionmentioning
confidence: 99%
“…The geographic variability observed in this association (30), the frequent clustering of resistant genotypes, and their successful spread within the Russian prison system (7,29) suggest recent clonal expansion. This is supported by evidence that some strains of the Beijing genotype family retain fitness despite the acquisition of drug resistance (28). The Haarlem genotype family has also been associated with drug resistance and rapid clonal expansion (8,19).…”
mentioning
confidence: 87%
“…A recent report in the Western Cape of South Africa showed that although MDR-TB was spreading by transmission, XDR-TB appeared to be acquired but not clonally derived (8). The diversity of the resistance mutations in Beijing strains has also been observed in Russia (9) and Japan (10), indicating independent acquisition. This is in contrast to the highly publicized outbreak of XDR-TB in HIV-positive individuals due to transmission in Tugela Ferry, South Africa.…”
mentioning
confidence: 99%